Analysis of The Mathematical Problem-Solving Ability on Two-Variable Linear Equation System Material In Grade VIII Students - Aulia, Syafa; Subarinah, Sri; Azmi, Syahrul; Amrullah, Amrullah (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study aims to describe the ability to solve mathematical problems on two-variable linear equation system material based on the locus of control in grade VIII students. This study used qualitative methods to obtain a sample of 72 students using purposive sampling. Data collection techniques use locus of control questionnaire instruments and problem-solving ability test questions. The results of this study showed that students with a strong external locus of control were only able to reach a step of understanding the problem. Meanwhile, students with a balanced internal and external locus of control can reach two steps namely, understanding the problems and devising a strategy. This happens because, students with a strong external locus of control, as well as students with a balanced internal and external locus of control, are less trying and less active in seeking information related to the problems at hand, and are easily influenced by others. Meanwhile, students with a strong internal locus of control can reach three steps namely, understanding the problems, devising a strategy, and carrying out the strategy. This happens because students have a strong internal locus of control easily satisfied with the results they get with the effort they make.